Multilevel Analysis on the Contextual Effect of Posyandu on Healthy Prenatal Behavior Among Pregnant Women in Bengkayang, West Kalimantan - Murdikawati, Dayang Fitri; Budihastuti, Uki Retno; Dewi, Yulia Lanti Retno (Journal of Maternal and Child Health, 2019)
Background: Evidence suggests that prenatal care, healthy behaviors such as exercise and nutrition, general stress level, and routine blood pressure examination, are associated with fetal and maternal health. However, there is a lack of studies on factors affecting these healthy prenatal behaviors in Indonesia. This study aimed to determine the contextual effect of posyandu on healthy prenatal behavior among pregnant women in Bengkayang, West Kalimantan Subjects and Method: A cross-sectional study was conducted at 25 integrated health posts (posyandu) in Bengkayang, West Kalimantan, from November to December 2018. A sample of 200 pregnant women was selected by simple random sampling. The dependent variable was healthy prenatal behavior. The independent variables were maternal education, family income, knowledge, health personnel support, family support, community leader support, and distance to posyandu. The data were collected by questionnaire and analyzed by multilevel logistic regression. Results: Healthy prenatal behavior was affected by maternal education (b= 4.64; 95% CI= 2.05 to 7.23; p<0.001), family income (b= 3.26; 95% CI= 1.15 to 5.37; p= 0.002), knowledge (b= 2.83; 95% CI= 0.90 to 4.47; p= 0.004), family support (b= 2.69; 95% CI= 0.70 to 4.69; p= 0.008), commu